Characteristics and effects of female hormones used by male transsexuals in Lima, Peru - Sánchez, Sixto (2014)
Introduction: In the feminization process, some male transsexuals use synthetic female hormones whose safety has not been defined in genetically male persons. Objectives: To evaluate the degree of knowledge, frequency of use, type of administration, adverse effects and source of information on female hormones in male transsexual persons. Design: Qualitative and quantitative community prospective study. Place: Lima. Participants: Male transsexuals 18 years old or older who had been using female hormones for 6 months or more. Interventions: Four trained male transsexuals identified new male transsexual by the ‘snow ball’ method. Then, subjects were interviewed, underwent physical examination, and a 10 mL blood sample was obtained. Main outcome measures: Level of knowledge, quality of information received, acquisition source, and side effects of female hormones. Results: Only 11.8% of the participants obtained the hormones by medical prescription and had some knowledge about its effects. Most common side effects were breast tenderness and weight gain (88.2%), and decline of libido and erection (58.8%). A combination of dihydroxyprogesterone plus estriol IM was the most common female hormone used (47.1%). Conclusions: Implementation of multidisciplinary services that meet the health needs of this population is necessary to decrease the risks.